O DIREITO FUNDAMENTAL DE PROPRIEDADE NOS CONDOMÍNIOS EDILÍCIOS EM TEMPOS DE PANDEMIA (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2020)
The pandemic caused by the new coronavirus led to the adoption of several sanitary measures, including in condominiums, affecting the fundamental property right. In this sense, the purpose of this article is to analyze the possibility of limiting the fundamental right of property, justifying themselves in view of its relevance. In order to achieve this purpose, the research was divided into three stages, namely: the analysis of the fundamental right of property; the possibility of restricting fundamental rights, from the perspective of proportionality; and the possible limitations to the fundamental property right in condominiums in times of pandemic. Using the deductive research method, it was intended to prepare a study including a theoretical analysis and the appreciation of cases recently decided by the Brazilian courts, considering, in the end, that any restriction on the property rights, even during the crisis caused by the COVID-19 virus, it must be adequate, necessary and observe proportionality in the strict sense, avoiding subjectivisms.